A Stakeholder-Centric Approach to Advancing the Circular Economy in the Building Sector - Fuat Emre Kaya (Architecture)
Since the Industrial Revolution, climate change has intensified due to rising greenhouse gas emissions, leading to severe environmental impacts. Given the building sector’s significant contribution to climate change, the circular economy has emerged as a key mitigation strategy. Despite political support and some advancements, significant barriers persist in the building sector’s transition to the circular economy. This article explores the pivotal role of stakeholders as essential agents of change, highlighting the necessity of a concentrated effort on stakeholder engagement in the building sector’s circular economy transition. Using an online questionnaire, this article evaluated the current status of the building sector, as well as stakeholders’ awareness, roles, and perspectives on the transition. The results revealed that while stakeholders are aware of their environmental impacts, knowledge gaps persist, particularly in waste management and circular economy practices. The stakeholders recognize that the transition is happening, but there is a sense of uncertainty about its effectiveness due to substantial barriers. Despite these barriers, there is an increasing commitment toward the practices of the circular economy, underscoring the need for policy development, infrastructure provision, and training programs to support the transition. This article contributes to the literature by providing insights into key stakeholders’ perspectives and offering actionable strategies to enhance engagement for a more effective transition to the circular economy in the building sector.